Unscramble the following limit laws. Let $f$ and $g$ be a function defined on some open interval that contains the number $a$, except possibly at $a$ itself, and suppose $\lim_{x\to a}\ f(x)$ and $\lim_{x\to a}\ g(x)$ exist. Let $c$ be a constant and $n$ a positive integer.
 $\lim_{x\to a}\ (f(x)+g(x))=$ $\lim_{x\to a}\ f(x)+\lim_{x\to a}\ g(x)$ $\lim_{x\to a}\ (f(x)\ -\ g(x))=$ $\lim_{x\to a}\ f(x)\ -\ \lim_{x\to a}\ g(x)$ $\lim_{x\to a}\ (cf(x))=$ $c\cdot\lim_{x\to a}\ f(x)$ $\lim_{x\to a}\ (f(x)g(x))=$ $\lim_{x\to a}\ f(x)\cdot\lim_{x\to a}\ g(x)$ $\lim_{x\to a}\ (\frac{1}{g(x)})=$ $\frac{1}{\lim_{x\to a}\ g(x)}$ if $\lim_{x\to a}\ g(x)\ne 0$ $\lim_{x\to a}\ (\frac{f(x)}{g(x)})=$ $\frac{\lim_{x\to a}\ \ f(x)}{\lim_{x\to a}\ g(x)}$ if $\lim_{x\to a}\ g(x)\ne 0$ $\lim_{x\to a}\ (f(x))^n=$ $(\lim_{x\to a}\ f(x))^n$ $\lim_{x\to a}\ c=$ $c$ $\lim_{x\to a}\ x=$ $a$ $\lim_{x\to a}\ x^n=$ $a^n$ $\lim_{x\to a}\ ^n\sqrt{x}=$ $^n\sqrt{a}$ $\lim_{x\to a}\ ^n\sqrt{f(x)}=$ $^n\sqrt{\lim_{x\to a}\ f(x)}$, assuming $\lim_{x\to a}\ f(x)>0$ for even $n$